Pelatihan Penggunaan Instagram Sebagai Media Pemasaran Digital Produk Ibu PKK Di Desa Sei Mencirim - Yunita Sari Siregar; Boni Oktaviana Sembiring; Herlina Harahap; Mufida Khairani; Hasdiana (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Sei Mencirim Village is one of the villages in Kutalimbaru District, Deli Serdang Regency, North Sumatra Province. Where in this village, there is a Family Welfare Development Women's Association (PKK) which plays a role in the field of culinary and handicraft empowerment training. In this community service, they carry out activities by utilizing social media Instagram in digital marketing of products produced by Mrs. PKK such as bags made from plastic waste and household processed cakes. Instagram is a social media that can display photos and videos and broadcast to anyone or in other words this social media can be watched by the wider community, so this social media is very good in product digital marketing media. The results of this training activity are expected to increase the additional income of PKK women from expertise in making handicrafts or processed foods.